A Review of Item Exposure Control Strategies for Computerized Adaptive Testing Developed from 1983 to 2005 - Georgiadou, Elissavet G; Triantafillou, Evangelos; Economides, Anastasios A (The Journal of Technology, Learning and Assessment, 2007)
Since researchers acknowledged the several advantages of computerized adaptive testing (CAT) over traditional linear test administration, the issue of item exposure control has received increased attention. Due to CAT’s underlying philosophy, particular items in the item pool may be presented too often and become overexposed, while other items are rarely selected by the CAT algorithm and thus become underexposed. Several item exposure control strategies have been presented in the literature aiming to prevent overexposure of some items and to increase the use rate of rarely or never selected items. This paper reviews such strategies that appeared in the relevant literature from 1983 to 2005. The focus of this paper is on studies that have been conducted in order to evaluate the effectiveness of item exposure control strategies for dichotomous scoring, polytomous scoring and testlet-based CAT systems. In addition, the paper discusses the strengths and weaknesses of each strategy group using examples from simulation studies. No new research is presented but rather a compendium of models is reviewed with an overall objective of providing researchers of this field, especially newcomers, a wide view of item exposure control strategies.